Increased Expression of VEGF and CD31 in Postradiation Rectal Tissue: Implications for Radiation Proctitis. (8th May 2013) - Karamanolis, G.; Delladetsima, I.; Kouloulias, V.; Papaxoinis, K.; Panayiotides, I.; Haldeopoulos, D.; Triantafyllou, K.; Kelekis, N.; Ladas, S. D.
Abstract : Background . Inflammation mediators related to radiation proctitis are partially elucidated, and neovascularization is thought to play a key role. Objectives . To investigate the expression of vascular endothelial growth factor (VEGF) and CD31 as angiogenetic markers in postradiation rectal tissue. Methods . Rectal mucosa biopsies from 11 patients who underwent irradiation for prostate cancer were examined immunohistochemically for the expression of VEGF and CD31 at three time settings—before, at the completion of, and 6 months after radiotherapy. VEGF expressing vascular endothelial cells and CD31 expressing microvessels were counted separately in 10 high-power fields (HPFs). VEGF vascular index (VEGF-VI) and microvascular density (MVD) were calculated as the mean number of VEGF positive cells per vessel or the mean number of vessels per HPF, respectively. Histological features were also evaluated. Results . VEGF-VI was significantly higher at the completion of radiotherapy (0.17 ± 0.15 versus 0.41 ± 0.24, P = 0.001 ) declining 6 months after. MVD increased significantly only 6 months after radiotherapy (7.3 ± 3.2 versus 10.5 ± 3.1, P < 0.005 ). The histopathological examination revealed inflammatory changes at the completion of radiotherapy regressing in the majority of cases 6 months after. Conclusions . Our results showed that in postradiation rectal biopsy specimens neoangiogenesis seems to be inflammation-related and constitutes a significant postradiation component of the tissue injury.